A systematic procedure for developing the 3D model to evaluate the construction project progress - Ahmed Memon, Zubair; Abd. Majid, Muhd. Zaimi; Mustaffar, Mushairry (Emerald Group Publishing Limited, 2007)

(untitled)
This main purpose of this study is to summarize the experience at the Construction Technology and Management Center (CTMC) to develop a Digitalizing Construction Monitoring (DCM) system by integrating 3DAutoCAD drawings and digital images. The objective of this paper is to propose a framework model for the DCM system and discuss in detail the steps involved for developing and calculating the 3D coordinate values from 2D digital images.